1997
DOI: 10.1029/97jd00845
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of organic trace gases from savanna fires in southern Africa during the 1992 Southern African Fire Atmosphere Research Initiative and their impact on the formation of tropospheric ozone

Abstract: Abstract. CO, CH4, and organic trace gases were measured in air samples collected during several flights with a DC-3 aircraft through the plumes from savanna fires and agricultural fires during the SAFARI 92 campaign in southern Africa in September and October 1992. In all samples a variety of higher molecular weight organic compounds was found, most of which are very reactive. More than 70 of the roughly 140 major components present could be identified. Typically, mixing ratios of several hundred parts per bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 34 publications
2
29
0
3
Order By: Relevance
“…Le Canut et al [34] study examined pre-harvest burning practices [41] and Yokelson et al [24] and Lopes and Carvalho [35] made reference to the sugarcane pre-harvest burning practice as a broadly used method to separate dried leaves and weeds from the sugarcane and to eliminate pests that could hinder manual harvesting.…”
Section: Resultsmentioning
confidence: 99%
“…Le Canut et al [34] study examined pre-harvest burning practices [41] and Yokelson et al [24] and Lopes and Carvalho [35] made reference to the sugarcane pre-harvest burning practice as a broadly used method to separate dried leaves and weeds from the sugarcane and to eliminate pests that could hinder manual harvesting.…”
Section: Resultsmentioning
confidence: 99%
“…For example Forstner et al (1997) have shown that in a smog chamber, carbon yields from even the most reactive NMHC species is less than 5%. However, recent studies have shown that oxygenated hydrocarbons account for more than 40% of the non-methane hydrocarbon emissions by biomass burning (Koppmann et al, 1997). Due to their high reactivity, these species are typically unreported and could be a large reservoir for secondary aerosol production.…”
Section: Particle Evolution Processesmentioning
confidence: 99%
“…A literature review of previous ground-and aircraft-based measurements of the CH 4 / CO 2 ER indicates a wide range of values, demonstrating the variability that can be dependent on not only the fuel type but also on additional factors, such as fuel moisture content, the ratio of living to dead matter and how recently the area last burned (Korontzi et al, 2003). To take just one example, Koppmann et al (1997) present CH 4 / CO 2 ER values for flaming fires of 2.6 ppb ppm −1 from sugar cane fields, increasing to 10.3 ppb ppm −1 over fires dominated by smouldering combustion in forest and shrubland. Fires with intermediate values were reported to represent a mixture of smouldering and flaming combustion.…”
Section: Fire Emissions and Combustion Regimesmentioning
confidence: 99%